Comparison of Hadith Thoughts of Sheikh Nuruddin Marbu Al-Makki and Ustadz Yazid bin Abdul Qadir Jawas - Irfan Padlian Syah; Ade Fakih Kurniawan; Ade Jaya Suryani (Yayasan Azhar Amanaa Yogyakarta, 2026)
This study aims to analyze and compare the hadith thought of Syekh Nuruddin Marbu Al-Makki Al-Banjari and Ustadz Yazid bin Abdul Qadir Jawas from methodological, epistemological, and practical perspectives. Both scholars represent contemporary Indonesian hadith scholars with different intellectual backgrounds and scientific orientations, yet both are highly influential in Indonesian hadith discourse. Sheikh Nuruddin Marbu represents the Haramain scholarly tradition rooted in the classical Nusantara scholarly chain of transmission (sanad), while Ustadz Yazid Jawas represents the Salafi orientation based on the methodology of contemporary Saudi Arabian scholars. This study employs a comparative-descriptive method, with critical discourse analysis applied to the primary works of both scholars. The results show fundamental differences in: (1) the epistemology of hadith acceptance, where Sheikh Nuruddin emphasizes sanad transmission and scholarly ijazah, while Ustadz Yazid focuses on matn authenticity based on Wahabi-Salafi jarh wa ta'dil criteria; (2) hadith criticism methodology, where Sheikh Nuruddin adopts an eclectic approach integrating classical and contemporary scholarly perspectives, while Ustadz Yazid tends to selectively follow scholars aligned with the Salafi orientation; (3) the application of hadith in Indonesian socio-religious contexts, where Sheikh Nuruddin is more accommodative toward local traditions, while Ustadz Yazid is more textualist-purificatory. This research contributes by filling the gap in comparative hadith research between traditionalist and Salafi Indonesian scholars, a topic that has not been previously studied with these specific figures.